Vigs invisier: ’n teologies-etiese besínning - Wyk, J. H. van (Koers, 1991)
In this article the characteristics of Aids are touched upon and then the (rather difficult) question whether Aids should be seen as God’s judgement over the sin (immorality) of man is discussed. Some typical aspects (sexual, medical, political and personal) are discussed and furthermore the line of argumentation is continued by elaborating on the calling of the church, the task of authorities and society as well as the responsibility of the family and the individual. The conclusion arrived at is that however serious the case of Aids may be, there is no room for pessimism, because Christians expect and await the full realisation of the kingdom of God This expectation does not nullify but maximises man’s responsibilty to fight Aids with all moral means at his disposal.